Arenas for Contentious Politics - Encarnacion Tadem, Teresa S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 23 No 1 (2008): Contentious Politics)
There is already a substantial literature on contentious politics. Still, the pertinence as well as the fluidity of such a phenomenon continues to merit deeper study as it gives birth to various dimensions of interest. The four articles in this issue offer differing vantage points in studying contentious politics as it is played out in the process of democratizing local and global politics. Social movement actors have emerged as key players in confronting political institutions and in articulating the advocacies of the marginalized. However, they are not always on the side of angels. Ben Reid’s “Development NGOs, Semiclientelism and the State in the Philippines: From ‘Crossover’ to Double-crossed” is a critique of how civil-society players in the Philippines have mirrored the clan-based politics and semi-clientelism that characterize society in general. This he elucidates as he discusses how non-governmental and people’s organizations have attempted to “crossover” to state positions in their attempt to initiate social and economic reforms. A more positive note on the role of civil society in the democratization process at the local and global levels is found in my contribution to this issue, “Linking Local and Global Social Movements and the anti-ADB Campaigns: From Chiang Mai to Samut Prakarn.” The article examines the factors that helped facilitate the linking of local and transnational social movements in the anti-Asian Development Bank (ADB) campaigns in the region. I point to the gains that they have attained in pressuring the ADB to look into their allegations concerning the ADB’s Samut Prakarn Wastewater Management Project in Thailand. They argued that this particular project has fallen short in meeting the good governance criteria, which has been set forth by the ADB as a result of decades of advocacy from social movements. These concern the issues of transparency and accountability and sustainability. The experience has shown that global civil society movements do play an important role in supplementing the efforts of local social movements, particularly in activating good governance mechanisms instituted by the ADB. However, some challenges remain. Local and global civil society movements still need to fine tune the dynamics of their relationship, to make it more responsive and adept at dealing with the politics at the local and global arenas of contention. Dealing with such arenas of contention is a reality as further seen in J. Shola Omotola’s “Democratization, Identity Transformation, and Rising Ethnic Conflict in Kogi State, Nigeria.” In his article, Omotola explores a major challenge to the democratization process: identity transformation and the rising ethnic conflicts in Kogi state. It highlights the important role of the state in empowering as well as disempowering people as they struggle to assert their respective ethnic identities resulting into an unsustainable form of democracy and development. For Omotola, an important solution to this is to institutionalize power sharing among the different competing ethnicity and minority groups. This of course is easier said than done, but like all the other articles in this issue, the fact that struggles continue in the search of a more just and equal society provides some optimism that, elusive as it may be now, the shifting form of challenges to democratization continues to be confronted. “Politics of the Great Debate in the 1950s: Revisiting Economic Decolonization in the Philippines” by Yusuke Takagi, on the other hand, brings us back into an era where only the oligarchical elites had a say on how Philippine economic policy would be. This is the essence of the Great Debate in the 1950s over fiscal and monetary policies including the foreign exchange policy. Although this is perceived to usher in the process of economic decolonization of the country, it was mainly an elite game. It was a clash of will and interests between the Central Bank governor and cabinet members identified with the so-called sugar bloc. It was a clash that conveniently positioned the Philippine president in the middle, acting as the great patron and arbiter. Further discussions on social movements and the relevance of contentious politics in liberal democracy can be found in the Proceedings and Perspectives sections of this issue. Kasian Tejapira, in his Violet Wurfel ASEAN Lecture, provided a brief yet insightful history on how the Thai social movements wrestled with the question of freedom and social justice. In the Perspectives Section, Anton L. Allahar, Dianto Bachriadi, John Markoff, and David S. Meyer, in separate yet congruent essays answered the question, “Is contentious politics relevant in liberal democracy?” This issue, therefore, highlights several themes and nagging concerns regarding the democratization process embedded at the local and global sites of engagement and confrontation.
Keywords: contentious politics